Socialization of Education on the Importance of Balanced Nutrition for the Young Generation in the Millennial Farmers Group of Kabul Village - Putri, Nydia Alisa; Ilmiati, Nur; Lestari, Dewi Putri; Sarjan, Achmad Fajar Natotama; Sarjan, Muhammad (Unram Journal of Community Service, 2024)
The millennial generation, a growing segment of Indonesia's youth, is expected to play a crucial role in the nation's future development. Thus, it is imperative to adequately prepare this resource, particularly by enhancing the quality of their education and health. Knowledge and understanding of health, especially nutrition, are critical for this group as it directly impacts their cognitive abilities. However, many young people still lack awareness of balanced nutrition, leading to various health. To address this, an educational outreach on the importance of balanced nutrition was conducted for the millennial farmer group in Kabul Village. The goal was to equip the youth with knowledge about balanced nutrition, influencing their eating habits and dietary patterns in the target village. The outreach employed educational methods, including material presentations by the team, interactive discussions, and summarizing the discussion outcomes. Monitoring results during the outreach indicated high participant interest, evidenced by numerous questions, particularly regarding parental roles in ensuring balanced nutrition for adolescent family members. Young participants highlighted the challenge of avoiding unhealthy snacks due to the proliferation of culinary trends and social media influences, often leading them to try foods without considering their nutritional value. The balanced nutrition education initiative aims to benefit both millennials and the older generation. Consequently, it is hoped that parents will emphasize balanced nutrition messages to their children within their families.